You are under arrest : epistemic arrest and the endless reproduction of the image of the colonised native - Farish Ahmad Noor (2021)
In the year 1907 the colonial entrepreneur and expert on tin-mining in British Malaya, CG Warnford-Lock, wrote thus in his book Mining in Malaya for Gold and Tin: From a labour point of view, there are practically three races: the Malays, the Chinese and the Tamils. By nature, the Malay is an idler, the Chinaman is a thief and the Indian is a drunkard. Yet each, in his special class of work, is both cheap and efficient, when properly supervised. (emphasis mine)1That the complexity of Malayan society, with its ethnically diverse population and its linguistic, cultural and religious differences, could be simply reduced to ‘practically three races’ that in turn bore three simple essential characteristics – idleness, criminality and drunkenness – is telling of how the order of knowledge and power that had dominated and defined the colony had also reduced its native inhabitants to stock caricatures that were permanently fixed and defined. Knowing the colonised native Other meant being in a position of epistemic leverage over that Other, and thus being able to define and frame the Other in whatever terms that suited the ideological needs of racialised colonial-capitalism at the time.